Efficacy of Video Prompting Using Mobile Technology to Teach Employment Tasks to Individuals with Intellectual Disability - Walters, Sharon; Stierle, Jordan; Stockwell, Daniel; Carlson, Alex; Ryan, Joseph (Journal of Inclusive Postsecondary Education, 2021)
Abstract Individuals with intellectual disability (ID) often experience a combination of both intellectual and adaptive functioning deficits which negatively impact their ability to obtain and maintain competitive employment. Fortunately, research has shown that assistive technology, and particularly video prompting, helps support employment for individuals with ID. This single case multiple probe study investigated the efficacy of a highly customizable task analysis smartphone application in assisting three young adults with ID complete common work-related office tasks. Findings indicate all three participants demonstrated very large effect size gains in completing three unique office-related tasks once provided with the Task Analysis app. Keywords: intellectual disability, assistive technology, employment, video prompting, mobile technology